Acid- and amide-controlled sol–gel synthesis of SiO2-based polymer composites - Azizova, M.P.; Aghahuseynova, M.M.; Mammadkhanova, S.A. (International Journal of Biology and Chemistry, 2025)
The sol–gel method is a versatile approach for synthesizing advanced inorganic and organic–inorganic hybrid materials with controlled structure, high purity, and tunable functionality. This study systematically investigated the hydrolytic polycondensation of tetramethoxysilane under acidic conditions to develop an optimized route for high-quality SiO2-based polymer–inorganic composites. The effects of medium acidity, catalyst type, solvent, and amide-based drying-control chemical additives (DCCA) on hydrolysis and condensation kinetics were evaluated. Strong acids accelerated hydrolysis, while weak acids promoted gradual condensation, yielding highly porous but mechanically weaker gels. Acetic acid facilitated homogeneous gel formation and improved transparency and pore uniformity by removing volatile ester by-products. Among the amides, dimethylacetamide and diethylformamide were found to be effective pH regulators in gelation, yielding dense, crack-free gels with lower microporosity and improved mechanical strength. SEM investigations have confirmed the more homogeneous, more compact structures of dimethylacetamide-containting gels, as compared with amide-free gels. Use of acetic acid as the solvent played an important role in controlling the micro-pores, carbon content, density, and stability of gels. In general, this work presents a comprehensive methodological approach for designing sol–gel SiO2-based hybrid nanomaterials with designed structural and physicochemical properties, with their potential use in advanced optical, catalysis, coatings, and other functional applications. Keywords: sol-gel process, tetrametoxysilane, hydrolysis, polycondensation, acidic environment.